Project Team Building: Case Study Investigation in the Construction Industry in Jordan - Dr. Hani Gharaibeh (International Journal of Engineering and Management Research, 2019)
Project teams play an important role in project performance. In the Engineering and Construction industry, the successful delivery of a project requires the collaboration of people with different skills and expertise which makes a healthy work relation among project team members very essential for the success of the project in particular and the organization in general. In this paper, we look at "Project team building" from three main dimensions: firstly, communication among project team members. Effectiveness of team communication in projects is becoming increasingly important due to the growing technical and organizational complexity of construction projects. Secondly, trust among project team members. Because trust is a major factor leading to the success or failure of construction project and finally, the role of leadership in project management, particularly in the construction field is very crucial to the success of the team. To achieve the above objective, we selected a case study investigation through which a major construction project in Jordan was analyzed. After studying the project related documents. We conducted several interviews and distributed several questionnaires asking key project stakeholders about the three dimensions of project team building defined. The study involved the identification of barriers and enablers for each dimension in the project team building model. The study concluded with a framework for project team building based on the dimensions of: trust, communication and leadership that could be applied on projects with similar context in Jordan.